Challenges in transfusion and the role of Thalidomide in E‐β‐Thalassemia—A case report. Issue 11 (30th July 2020) - Javed, Rizwan; Radhakrishnan, Vivek; Basu, Sabita; Chandy, Mammen
Abstract: Hemoglobin E‐β‐thalassemia is a common β‐thalassemia that has a variable presentation from mild to severe life‐threatening anemia. We describe such a case, who presented with severe anemia and multiple allo‐antibodies. Our case illustrates the role of thalidomide in transfusion‐sparing therapies in patients with transfusion‐dependent thalassemia and challenges in the blood bank. Abstract : The role of thalidomide in transfusion‐sparing therapy in a transfusion‐dependent E‐β‐thalassemia patient. Thalidomide acts as a fetal hemoglobin inducer and alleviates alloimmunization by immunomodulation.